Systematic review: genotypic and phenotypic resistance of fluoroquinolone-resistant Salmonella in livestock in South America (2020–2024) - Barrientos-Villegas, Stefany; García-Álvarez, María Isabel; Vidal, Juana L.; Gómez-Osorio, Luis M.; López-Osorio, Sara; Chaparro-Gutiérrez, Jenny J. (Frontiers in Veterinary Science, 2025)
ObjectiveTo determine the frequency of phenotypic and genotypic resistance to quinolones and fluoroquinolones in Salmonella spp. isolated from production animals (pigs, poultry, cattle) and rodents in South America between 2020 and 2024, with the goal of providing key information on resistance in these countries for public health and food safety.MethodsA systematic review was conducted following the PRISMA guidelines, using databases such as Scopus, PubMed, SciELO, and Latindex. Studies on Salmonella spp. resistant to quinolones and fluoroquinolones in production animals, meat products, and rodents in South America during 2020–2024 were included.ResultsOf the 83 initial results, 27 studies were selected. 70.4% of the studies were conducted in Brazil. 88% of the studies (n = 24/27) used phenotypic methods, with the disk diffusion technique being the most common. Ciprofloxacin was the most studied antibiotic, with an overall resistance of 32.5%, followed by nalidixic acid (60.6%) and enrofloxacin (23.7%). The average multidrug resistance (MDR) was 62%. 44% of the studies (n = 12/27) employed genotypic methods, with whole genome sequencing (WGS) being the most notable technique. Mutations were reported in parC (58%), gyrA (50%), gyrB (8%), and the presence of qnr genes (75%) and aac(6′)-Ib-cr (8%). No studies on rodents were found.ConclusionResistance to quinolones and fluoroquinolones in Salmonella spp. in South America endangers public health and food safety. To address antimicrobial resistance, monitoring and control measures must be implemented, regional research should be promoted, and stronger restrictions should be enforced.